Comparison of demographic and virological profiles between diabetic and non-diabetic patients with cirrhosis of liver (BIRDEM Medical Journal, 2019)
Background: Cirrhosis of liver is the most common cause of liver disease in our country. It is an important cause of mortality and morbidity. Hepatitis B and Hepatitis C virus infection are the important causes of liver disease in our country. Many people present to us with established cirrhosis of liver. The aim of our study is to compare the demographic and virological profiles between diabetic and non-diabetic patients with cirrhosis of liver.Methods: This cross-sectional study was carried out from July 2018 to December 2018 in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital and in Supreme Medical Services, Jatrabari, Dhaka. Cirrhosis of liver was diagnosed with the help of ultrasonography of whole abdomen, endoscopy of upper gastro-intestinal tract (GIT), fibroscan of liver and liver biopsy where indicated.Results: Total 465 cases were enrolled in this study. Of them 272 patients were diabetic and 193 patients were non- diabetic. The study reached its various findings from the view point in our country. Most diabetic patients were between the age 51 to 60 (57.4%) and in non-diabetic patients between the age 41 to 50 (31.1%) (p